INCORPORATING CALL IN PROMOTING LEARNER AUTONOMY-A STUDY CONDUCTED IN THE REPUBLIC OF KOSOVA - Maliqi, Flora (PEOPLE: International Journal of Social Sciences, 2016)
The aim of this paper is to highlight the role of computer assisted language in promoting learner autonomy. This study was conducted in three secondary schools in the Republic of Kosova in Gjilan city. The significance of this study is to raise teachers and learners’ awareness in promoting learner autonomy in their teaching and learning process. The participants of this study were 300 students and 30 English teachers. Students participated by completing the questionnaire which consisted of 27 questions and teachers gave their opinions about this topic by giving responses to 10 questions. Learners identified their beliefs and attitudes towards the use of CALL in promoting learner autonomy. Computer Assisted Language Learning (CALL) appears to be very helpful in fostering learner autonomy, since it includes different useful components of autonomy. It allows learners to take control and responsibility for their own task by selecting their preferred materials, and assessing their own development. However, although it seems that the term learner autonomy is a new concept in this city the findings indicate that participants use computers a lot for educational purposes and are positive regarding to the use of them in promoting learner autonomy. It is concluded that learners consider CALL as a great facilitator in language learning but in order to get its maximum effectiveness the findings show that learners need their teachers support. They claim that the role of the teacher is very important in guiding them to the best ways on how to use CALL in order to become autonomous learners.